Core Fucosylation Regulates the Function of Pre-BCR, BCR and IgG in Humoral Immunity - Sun, Yuhan; Li, Xueying; Wang, Tiantong; Li, Wenzhe (Frontiers in Immunology, 2022)
Most of the membrane molecules involved in immune response are glycosylated. N-glycans linked to asparagine (Asn) of immune molecules contribute to the protein conformation, surface expression, stability, and antigenicity. Core fucosylation catalyzed by core fucosyltransferase (FUT8) is the most common post-translational modification. Core fucosylation is essential for evoking a proper immune response, which this review aims to communicate. First, FUT8 deficiency suppressed the interaction between μHC and λ5 during pre-BCR assembly is given. Second, we described the effects of core fucosylation in B cell signal transduction via BCR. Third, we investigated the role of core fucosylation in the interaction between helper T (TH) cells and B cells. Finally, we showed the role of FUT8 on the biological function of IgG. In this review, we discussed recent insights into the sites where core fucosylation is critical for humoral immune responses.